Voice Over Wlans : - Finneran, Michael F. (Elsevier/Newnes, 2008)
Wireless local area networks (WLANs) have traditionally been used to transport only data, but are now being used to carry voice traffic as well as provided new combined voice and data services. Voice over WLANs also offers more flexibility than wired networks (changes to a WLAN don't require changes to installed wiring) and greater capacity than wired networks. This book provides a solid overview of voice over WLANs/VoIP (voice over internet protocol) technology, including voice coding, packet loss, delay and "jitter," and "echo" control. It shows how to combine both WLAN and VoIP technology to create effective voice over WLAN systems.